Non-isothermal crystallization kinetics of cork-polymer composites for injection molding - Magalhães da Silva, Sara P.
The non-isothermal crystallization behavior of cork–polymer composites (CPC) based on polypropylene (PP) matrix was studied. Using differential scanning calorimetry (DSC), the crystallization behavior of CPC with 15 wt % cork powder at different cooling rates (5, 10, 15, and 20 °C/min) was studied. The effect of a coupling agent based on maleic anhydride was also analyzed. A composite (PPg) containing polypropylene grafted maleic anhydride (PPgMA) and PP was prepared for comparison purposes. Crystallization kinetic behavior was studied by Avrami, Ozawa, Liu, and Kissinger methods. The Ozawa method fails to describe the behavior of these composites. Results show that cork powder surface acts as a nucleating agent during non-isothermal crystallization, while the addition of PPgMA decreases the crystallization rate.